PERGESERAN SISTEM PERNIKAHAN ENDOGAMI MASYARAKAT ETNIS BUGIS - A. Dian Fitriana; Khaerun Nisa' (Balai Penelitian dan Pengembangan Agama Makassar, 2020)
Endogamy or marriage in family clumps or known as in-marriage is one way to maintain kinship relations in Bugis society. The purpose of this research is to know the development of the endogamous marriage system adopted by Bugis ethnic society to the present. This research uses qualitative method with fenomenology approach. The subject of this research consisted of six pairs of husband and wife who had mixed ethnic marriages. The results showed that the contemporary Bugis extended the boundaries of endogamy, from within close and extended families (cousins) to Bugis from the same village, and eventually to ethnic Bugis generally. But over the times, technology and time have been able to erode the endogamous marriage system that was originally adopted by the Bugis ethnic society. There are several reasons that affect Bugis endogamous marriage system, such as the background of parents who choose to marry different cultures, gender (males who have more influence to determine the spouse), characters and prospective spouse's work.